Minecraft for makers : Minecraft in the real world with LEGO, 3D printing, Arduino, and more! - Baichtal, John (Maker Media, 2017)
Minecraft for Makers explores the intersection of this creative and beloved electronic game with the real world. It gives readers the opportunity to take familiar objects from the game - such as blocks, jack o'lanterns, and mobs - and make real-world versions of them. Begin with simple crafting projects using wood, paint, and LEGOs. Then move up to projects that involve basic electronics with LEDs. And, finally, advance to Arduino microcontroller projects that teach programming skills and basic robotics. The skills build progressively on one another, from chapter to chapter, and the emphasis is on fun all the way!